The potential of written and spoken word poetry to support meaning making and recovery for people who have experienced psychosis - Pearson, Mark (2023)
Background As a medium of communication, poetry can evoke, narrate, and translate lived experience into words. Although there is a body of research that has examined how poetry might be beneficial as an intervention for people with mental health problems, there remains a dearth of research exploring the therapeutic potential of poetry for people who have experienced psychosis. The biological paradigm of mental illness, which has traditionally orientated the treatment of psychosis is currently in a state of crisis, providing the opportunity for novel and potentially poetic alternative paradigms to emerge.